Reconstructing Corporate Opportunity Doctrine in Indonesia: Addressing Legal Vacuum and Fiduciary Duty - Rolis Barson Sembiring (CV. Era Digital Nusantara, 2026)
The absence of explicit provisions governing the Corporate Opportunity Doctrine in Indonesian Company Law creates a critical legal vacuum, exacerbating agency costs and facilitating fiduciary duty breaches. Opportunistic directors frequently exploit this regulatory void, weaponizing the Business Judgment Rule as a safe harbor against tort claims. Through a functional comparative approach, this article examines mandatory disclosure frameworks in the United States and strict prophylactic rules in Singapore to evaluate fiduciary boundaries. The analysis demonstrates that effective corporate governance requires precise operational limits and absolute transparency. To resolve this doctrinal deadlock, this study proposes a legislative reconstruction by integrating the doctrine into the unique dual board system of Indonesia. The proposed framework mandates proactive disclosure and independent corporate rejection by the Board of Commissioners. Furthermore, introducing disgorgement of profits as an equitable remedy is essential to restore legal certainty, mitigate managerial misconduct, and fully align national corporate governance with rigorous global standards.